Analysis of cycloid type vacuum compressors for water vapor compression systems at sub-atmospheric pressures. (August 2019) - Moesch, T W; Janitschke, T; Thomas, C; Hesse, U
Abstract: Current refrigerant regulations lead to a transition towards low GWP refrigerants and natural refrigerants. Water vapor (R718) has been introduced in different vapor compression chiller and heat pump systems. Current R718 systems are based on turbo type compressors due to the resulting sub-atmospheric operating pressure and the low volumetric cooling capacity. This leads to a rather limited application range due to the pressure ratio limitations of turbo compressors. The application range of R718 may be extended towards heat pump operation by using positive displacement compressors such as state of the art vacuum compressors. This paper analyses the application of an oil free cycloid type variable pitch screw vacuum compressor for a heat pump at 2…15 °C evaporation temperature and 25…85 °C condensing temperature. A chamber model was used for the compressor analysis. During the analysis the compressor geometry, its speed and leakage gap sizes were varied. The results include the compressor isentropic efficiency, its volumetric efficiency and the resulting discharge temperature.